KESADARAN TOLERANSI ANTAR-UMAT BERAGAMA DI KALANGAN MAHASISWA UNIVERSITAS ISLAM MALANG BERDASARKAN PANCASILA - Aprilia Dwi Rasdiyanti (Jurnal Penelitian Humaniora, 2019)
The technological era has developed many conveniences in social communication, digital economy, and national information. The ease between individuals to exchange information also has a negative. The limits of freedom released make unity is divided. The diversity of religions, ethnicities and races in Indonesia is a national heritage that must be maintained by all young people, including students in college. Pancasila education is one way to create nationalism and ownership of the state in the life of the nation and state. The problem raised in this article is how much awareness among religious people between students and how solutions to strengthen inter-religious awareness among students in college. In this study, primary data were obtained from a questionnaire. The questionnaire used was a questionnaire that was open in nature. From the research, the results show that almost all respondenn understand and aware of about inter-religious groups in Indonesia